The Philosophy of Law as a Gateway to Understanding Law - Asa, Agam Ibnu; Shidarta, Shidarta (Fakultas Hukum Universitas Islam Jakarta, 2025)
The philosophy of law plays a foundational role in conceptualizing law beyond its formal structure as written rules, particularly in legal systems marked by tensions between positive law and substantive justice, such as Indonesia. This study examines how philosophy of law functions as an epistemic gateway to understanding the nature, authority, and normative grounding of law by integrating classical and modern jurisprudential traditions. Employing a juridical-philosophical method with a qualitative-descriptive approach based on doctrinal and theoretical analysis, the research engages natural law theory, legal positivism, legal realism, and critical approaches. The findings indicate that the relationship between law and morality cannot be reduced to a rigid dichotomy; instead, these traditions provide complementary analytical frameworks for assessing legal validity, legitimacy, and justice. By situating these perspectives within Indonesia’s plural legal context, the study demonstrates the continuing relevance of philosophical inquiry for legal interpretation and institutional reform. It concludes that strengthening philosophical foundations in legal education is essential to foster reflective legal reasoning and to bridge the gap between formal legality and substantive justice.